Neglected foreign bodies in the nasal cavity: a unique case series and review - Thakkar, Himanshu (International Journal of Contemporary Pediatrics, 2025)
Foreign bodies in the nasal cavity are frequently encountered in pediatric populations, often due to accidental insertion. Typically, these foreign bodies become lodged in either the anterior (vestibular) or, less commonly, posterior (choanal) regions of the nasal cavity. Although diagnosis is usually straightforward, it can be challenging in the absence of a clear history, especially in young children. In our case series, no history of foreign body insertion was available; diagnosis was prompted by clinical signs such as unilateral nasal discharge, nasal obstruction, and occasional epistaxis. The nature of the foreign bodies varied, and removal was sometimes complicated by the risk of associated complications. This study presents several cases of neglected nasal foreign bodies identified during routine outpatient evaluations at our institute. These objects had remained undiagnosed for prolonged periods and were ultimately detected through endoscopic examination. Most patients were children aged 3 to 10 years. Although literature on nasal foreign bodies is limited and usually spans short follow-up periods (typically 3 months to 5 years), imaging—particularly CT scans—plays a vital role in accurate diagnosis. Management generally involves surgical removal, with endoscopic techniques now preferred due to their safety and efficacy. In asymptomatic cases, periodic radiographic follow-up may be sufficient.